Digital Financial Innovation's Impact, Cash Holding, and Investment Efficiency on Firm Size as a Moderating Variable and Firm Value via Financial Flexibility - Desita Mustikasari Wijayanti; Imelda Mutiara Chandra; Merryscha Putri Az Zahra; Nina Nor Fadilah; Ulfa Ulfa; Tiffany Shahnaz Wati; Maria Yovita R. Pandin (International Journal of Economic and Business Research, 2026)
This study aims to examine the effect of Digital Financial Innovation, Cash Holding, and Investment Efficiency on Firm Value, both directly and indirectly through Financial Flexibility as a mediating variable, as well as Firm Size as a moderating variable. A quantitative approach was employed using secondary data from companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. The sample was selected using purposive sampling, resulting in 30 firms with 90 firm-year observations. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results show that Digital Financial Innovation and Investment Efficiency do not have a significant direct effect on Firm Value, but both have a positive and significant effect on Financial Flexibility. Cash Holding is found to have a positive and significant effect on both Firm Value and Financial Flexibility. However, Financial Flexibility does not significantly affect Firm Value and does not mediate the relationship between the independent variables and Firm Value. Firm Size also has no significant effect on Firm Value and does not moderate the relationship between Financial Flexibility and Firm Value, acting only as a predictor variable. These findings highlight the importance of liquidity management and digital readiness in strengthening corporate financial resilience. Investors should consider liquidity, digital strategy, and financial structure beyond firm size.